As Violence Unfolds: A Space–Time Study of Situational Triggers of Violent Victimization Among Urban Youth - Dong, Beidi; Morrison, Christopher N.; Branas, Charles C.; Richmond, Therese S.; Wiebe, Douglas J. (Journal of quantitative criminology, 2020)
Objectives This study clarifies three important issues regarding situational or opportunity theories of victimization: (1) whether engaging in risk activities triggers violent assault during specific, often fleeting moments, (2) how environmental settings along individuals’ daily paths affect their risk of violent assault, and (3) whether situational triggers have differential effects on violent assault during the day versus night. Methods Using an innovative GIS-assisted interview technique, 298 young male violent assault victims in Philadelphia, PA described their activity paths over the course of the day of being assaulted. Case-crossover analyses compared each subject’s exposure status at the time of assault with his own statuses earlier in the day (stratified by daytime and nighttime). Results Being at an outdoor/public space, conducting unstructured activities, and absence of guardians increase the likelihood of violent victimization at a fine spatial–temporal scale at both daytime and nighttime. Yet, the presence of friends and environmental characteristics have differential effects on violent victimization at daytime versus nighttime. Moreover, individual risk activities appeared to exhibit better predictive performance than did environmental characteristics in our space–time situational analyses. Conclusion This study demonstrates the value of documenting how individuals navigate their daily activity space, and ultimately advances our understanding of youth violence from a real-time, real-life standpoint.